Iraqi press after World War II 1946-1958 Freedom of the press in light of the United Nations Charter and the Universal Declaration of Human Rights (Journal of the College of Basic Education, 2022)
Iraq witnessed, after the end of World War II and the establishment of the United Nations, internal political openness and revival of democratic life, which was represented by: the establishment of public political parties, the press enjoying relative freedom, and the emergence of new newspapers, but that did not last long, as a result of the conduct of the authorities which was contrary to the principles of democracy and human rights guaranteed by the Universal Declaration of 1948. Iraq successive government authorities exploited, between (1946-1958), the political conditions which were experienced by Iraq to declare martial law for more than once, and by which, they eliminate all kinds of freedoms, particularly the freedom of the press, through prior censorship exercised by them. The last attack which the government did to the press was issuing the Decree 24 of 1954, which abolished the privilege of all the newspapers at the time, which were estimated up to two hundred newspapers and magazines, and the government did not grant any privileges except for seven newspapers, four of them were in favor of the government policy, which continued until the fall of the monarchy